Relationship between stress hyperglycemia ratio and allcause mortality in critically ill patients: Results from the MIMIC-IV database - Zhang, Chong; Shen, He-Chen; Liang, Wei-Ru; Ning, Meng; Wang, Zi-Xuan; Chen, Yi; Su, Wei; Guo, Ting-Ting; Hu, Kun; Liu, Ying-Wu (Frontiers in Endocrinology, 2023)
Background: Stress hyperglycemia ratio (SHR) was developed to reduce the impact of long-term chronic glycemic factors on stress hyperglycemia levels, which have been linked to clinical adverse events. However, the relationship between SHR and the short- and long-term prognoses of intensive care unit (ICU) patients remains unclear. Methods: We retrospectively analyzed 3,887 ICU patients (Cohort 1) whose initial fasting blood glucose and hemoglobin a1c data within 24 hours of admission were available and 3,636 ICU patients (Cohort 2) who were followed-up for 1-year using the Medical Information Mart for Intensive Care IV v2.0 database. Patients were divided into two groups based on the optimal cutoff value of SHR, which was determined using the receiver operating characteristic (ROC) curve. Results: There were 176 ICU deaths in Cohort 1 and 378 patients experienced all-cause mortality during 1 year of follow-up in Cohort 2. The results of logistic regression revealed that SHR was associated with ICU death (OR 2.92 [95% CI 2.14–3.97] P < 0.001), and non-diabetic patients rather than diabetic patients showed an increased risk of ICU death. As per the Cox proportional hazards model, the high SHR group experienced a higher incidence of 1-year all-cause mortality (HR 1.55 [95% CI 1.26–1.90] P < 0.001). Moreover, SHR had an incremental effect on various illness scores in predicting ICU all-cause mortality. Conclusion: SHR is linked to ICU death and 1-year all-cause mortality in critically ill patients, and it has an incremental predictive value in different illness scores. Moreover, we found that non-diabetic patients, rather than diabetic patients, showed an increased risk of all-cause mortality.